2006
DOI: 10.1104/pp.106.087023
|View full text |Cite
|
Sign up to set email alerts
|

Xylella fastidiosa Infection and Ethylene Exposure Result in Xylem and Water Movement Disruption in Grapevine Shoots

Abstract: It is conventionally thought that multiplication of the xylem-limited bacterium Xylella fastidiosa (Xf) within xylem vessels is the sole factor responsible for the blockage of water movement in grapevines (Vitis vinifera) affected by Pierce's disease. However, results from our studies have provided substantial support for the idea that vessel obstructions, and likely other aspects of the Pierce's disease syndrome, result from the grapevine's active responses to the presence of Xf, rather than to the direct act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 33 publications
4
72
1
Order By: Relevance
“…Host ethylene perception and synthesis have been previously shown to be an important factor in development of wilt symptoms elicited by fungal vascular pathogens (Van der Molen et al, 1983;Lund et al, 1998;Robison et al, 2001). Interestingly, ethylene treatment of various plant species causes xylem occlusion, which leads to the wilt phenotype of vascular diseases (Van der Molen et al, 1983;Perez-Donoso et al, 2007). In addition, it was shown that ethylene produced by galls of Agrobacterium-infected tomato plants decreases the diameter of xylem vessels in the stem adjacent to the tumor (Aloni et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Host ethylene perception and synthesis have been previously shown to be an important factor in development of wilt symptoms elicited by fungal vascular pathogens (Van der Molen et al, 1983;Lund et al, 1998;Robison et al, 2001). Interestingly, ethylene treatment of various plant species causes xylem occlusion, which leads to the wilt phenotype of vascular diseases (Van der Molen et al, 1983;Perez-Donoso et al, 2007). In addition, it was shown that ethylene produced by galls of Agrobacterium-infected tomato plants decreases the diameter of xylem vessels in the stem adjacent to the tumor (Aloni et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen infection has been reported to cause elevated ethylene production of host plants in many species (Pegg, 1976;Pegg and Cronshaw, 1976;Boller, 1991;Abeles et al, 1992), including grapevines infected with X. fastidiosa (Pérez-Donoso et al, 2007). Furthermore, ethylene promotes tylose formation in grapevines (Sun et al, 2007) and pectin gel accumulation in other species (VanderMolen et al, 1983).…”
Section: Vascular Occlusions In Relationship To Disease Resistance/sumentioning
confidence: 99%
“…Even though the specific mechanistic linkage of wounds and enhanced ethylene synthesis is not clear in all plant systems, it is easy to propose that the harm caused by pathogens like X. fastidiosa could be perceived as a biochemical/structural wound by the infected grapevine. Furthermore, because disruption of the cell wall PM fabric catalyzed by the bacterium's CWDEs occurs during PD development (Pérez-Donoso et al, 2007;Sun et al, 2011), it is reasonable to suggest that pectinderived oligosaccharides, generated by PG cleavage of the sparsely methylesterified homogalacturonans in the PMs, could be a signal intermediate. Such oligosaccharides are known to be generated in ripening tomato fruit and to promote fruit ethylene synthesis (Melotto et al, 1994).…”
Section: Vascular Occlusions In Relationship To Disease Resistance/sumentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the availability of NMR, studies using this technology are largely focused to the spread of embolism over long periods of time (e.g. weeks [Umebayashi et al, 2011] or months [Pérez-Donoso et al, 2007]) rather than the shortterm dynamics of embolism spread over the course of a few hours.…”
mentioning
confidence: 99%